Microstructure and mechanical behavior of Mg/Al composite plates with different thicknesses of Ti foil interlayer - Jian Li; Bo Feng; Xiaowei Feng; Xianhua Chen; Kaihong Zheng; Xianquan Jiang; Fusheng Pan (Journal of Magnesium and Alloys)
In this study, microstructure and mechanical behavior of Mg/Al composite plates with Ti foil interlayer were systematically studied, with a great emphasis on the effect of different thicknesses of Ti foil interlayer. The results show that compared to 100 µm thick Ti foil, 10 µm thick Ti foil is more prone to fracture and is evenly distributed in fragments at the interface. The introduction of Ti foil can effectively refine the grain size of Mg layers of as-rolled Mg/Al composite plates, 10 µm thick Ti foil has a better refining effect than 100 µm thick Ti foil. Ti foil can effectively increase the yield strength (YS) and ultimate strength (UTS) of as-rolled Mg/Al composite plates, 10 µm thick Ti foil significantly improves the elongation (El) of Mg/Al composite plate, while 100 µm thick Ti foil slightly weakens the El. After annealing at 420 °C for 0.5 h and 4 h, Ti foil can inhibit the formation of intermetallic compounds (IMCs) at the interface of Mg/Al composite plates, which effectively improves the YS, UTS and El of Mg/Al composite plates. In addition, Ti foil can also significantly enhance the interfacial shear strength (SS) of Mg/Al composite plates before and after annealing.